Accuracy Improvement for Indoor Positioning Using Decawave on ESP32 UWB Pro with Display and Regression - Hapsari, Gita Indah; Munadi, Rendy; Erfianto, Bayu; Irawati, Indrarini Dyah (Universitas Muhammadiyah Yogyakarta, 2024)
In UWB-based indoor positioning, it is important to observe the ranging performance of the UWB module to prevent positioning errors. Ranging is the initial process in computing positioning. This research aims to observe the ranging accuracy and precision of the ESP32 UWB Pro with a Display module and analyze its performance in indoor positioning using TDoA and Trilateration. The ranging method was held using the SS-TWR which is the basic ranging used generally in UWB. ESP32 Pro is a module consisting of ESP32 and OLED display which is integrated with Decawave DW 1000. Analysis of 6750 ranging error data is carried out to determine the appropriate method to increase accuracy. The convergence of error ranges that occur leads to the use of regression as an error mitigation method for Decawave on the ESP32 UWB Pro with Display module. Increasing the accuracy of ranging regression can reduce the error from MAE of 79.98cm to only 5.05cm. It’s applied to positioning to obtain the accuracy and precision performance of the TDoA and Trilateration positioning. The resulting MAE values are 7.47cm for X and 10.49cm for Y in TDoA Positioning. Meanwhile, in Trilateration, the MAE was 8.15cm for X and 8.47cm for Y. Our findings indicate that an increase in ranging accuracy with regression had an impact on positioning accuracy. However, the spread of error positioning shows that it’s still weak in precision.